Análise energética, exergética e tecnoeconômica de um sistema de condicionamento de ar baseado na regulação natural da energia solar em condições climáticas da Amazônia - SANTOS, Elson Costa dos (Universidade Federal do Pará, 2023)
This work investigates the behavior of a photovoltaic air conditioning system, without batteries or connection to the electrical grid, operating according to the natural regulation of solar energy, in climatic conditions in the Amazon, a region with significant energy challenges, where in many locations, children, adolescents, adults and the elderly live without one of the main inputs for the development of productive, educational, leisure and even subsistence activities. The simulation results indicate that a system powered by a 1400 Wp photovoltaic generator can maintain thermal comfort conditions, with temperatures between 20 °C and 26 °C and relative humidity between 40% and 80%, for almost half of the operating time. and without any active control. Exergy analyses reveal variations in efficiency and irreversibility of components throughout the day, with the greatest impact on the photovoltaic system, followed by the compressor, condenser, evaporator, and expansion valve. Furthermore, the economic analysis shows that the implementation of these systems in parallel to systems powered by the conventional electrical grid can reduce grid energy consumption by 60.76%, and is strongly related to the tariff charged by the energy concessionaire. Finally, the research demonstrates the use of photovoltaic air conditioning systems as a sustainable solution for cooling, showing its effectiveness with the natural regulation of solar energy and its economic contribution to reducing the consumption of non-renewable energy